The interplay of interest rates and debt-financed government spending - Bev G. Dahlby; Ergete Ferede (CESifo GmbH, 2023)
Proponents focus on the average fiscal cost of program spending when the interest rate on government debt is less than the economy's growth rate. They ignore the potentially large marginal fiscal cost of deficit-financed increases in spending that arise when a higher public debt increases interest rates on government debt and lowers growth rates.
Keywords: 330